TRANSITIVITY ANALYSIS OF SEXUAL-RELATED LANGUAGE IN EKA KURNIAWAN’S CANTIK AND ITS ENGLISH VERSION - Dwi Husba; Abdul Hakim Yassi; Noer Jihad Saleh (JURNAL ILMU BUDAYA, 2021)
The objective of this study is to analyse transitivity system of sexual-related language in Eka Kurniawan’s Cantik itu Luka and its English version. This study employs qualitative method. There are 430 data of sexual related-language in Eka Kurniawans’ Cantik itu Luka and its English version. Each of version is 215. Data were collected by reading Indonesian and English version, identifying the related terms, analysing and comparing the sample, and drawing the conclusion. The collected data were analysed by using transitivity analysis proposed by Halliday. From 215 data of each version, the writer only analysed 213 clauses for each since there were two clauses were incomplete and untranslated so they could not be taken as sample of data. From transitivity analysis, it was found that the dominant process was material process both in Indonesian and English version. Kata Kunci : transitivity, sexual-related language, Cantik itu Luka, Beauty is A Wound.